Analysis of Arabic Learning in Homeschooling Sidoarjo Regency - Nadia Salsabyla; Farikh Marzuki Ammar (Indonesian Journal of Islamic Studies, 2023)
This is because this educational model can be implemented according to the needs of parents and children. Starting from the teacher, curriculum, syllabus, subjects to study time can be adjusted to the needs of learning. The purpose of this study was to determine the process of learning Arabic, the supporting and inhibiting factors of learning, and problems in learning Arabic at Homeschooling Mutiara Ummah Sidoarjo. The research method used is descriptive qualitative research with data collection techniques through field studies using observation, interviews and documentation. The data analysis technique used is interactive analysis which consists of three parts, namely data reduction, data presentation, and conclusions. From the results of the study, it is known that learning Arabic uses the book of al arabiya baina yadaik volumes one and two. Some of the factors that support learning include 1) a curriculum that is not linked to the National Education Office, so that schools are more flexible in choosing materials that suit the needs and abilities of students. 2) teachers who are creative in classroom management so as to create a conducive learning atmosphere. 3) dormitory activities that help students' language skills. 4) LCD projector facilities. The inhibiting factors for learning consist of language and non-language factors